2012
DOI: 10.1534/genetics.111.133447
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Heterosis: Multiparental Quantitative Trait Loci Mapping Reveals Contrasted Levels of Apparent Overdominance Among Traits of Agronomical Interest in Maize (Zea mays L.)

Abstract: Understanding the genetic bases underlying heterosis is a major issue in maize (Zea mays L.). We extended the North Carolina design III (NCIII) by using three populations of recombinant inbred lines derived from three parental lines belonging to different heterotic pools, crossed with each parental line to obtain nine families of hybrids. A total of 1253 hybrids were evaluated for grain moisture, silking date, plant height, and grain yield. Quantitative trait loci (QTL) mapping was carried out on the six famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
108
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 54 publications
22
108
2
1
Order By: Relevance
“…S30). QTLs with significant effect on seven of nine key domestication traits are located on chromosome 5 (7), and several QTLs for important agronomic traits (35), including plant height (36) and yield (37), map near CEN5.…”
Section: Low Genetic Diversity At Most Maize Centromeresmentioning
confidence: 99%
“…S30). QTLs with significant effect on seven of nine key domestication traits are located on chromosome 5 (7), and several QTLs for important agronomic traits (35), including plant height (36) and yield (37), map near CEN5.…”
Section: Low Genetic Diversity At Most Maize Centromeresmentioning
confidence: 99%
“…Several dominantly acting loci have been shown to contribute to heterosis (29,77,78), and more recently, heterosis-associated loci in maize have been shown to be enriched for deleterious mutations (43). Although dominance remains the prevailing explanation, some assumptions of this hypothesis are not consistently supported; the correlation between the degree of heterosis and the genetic distance between parents is not always evident (37,(55)(56)(57)(79)(80)(81)(82), and there are loci with moderate effect sizes (29,77,78).…”
Section: Arabidopsis Thaliana In the Context Of Traditional Heterosismentioning
confidence: 99%
“…Initial QTL studies indicated many QTL with overdominant gene action in populations derived from heterotic maize hybrids for traits such as yield and plant height [37,38]. However, subsequent genetic dissection of an QTL with estimated overdominant gene action showed that the original QTL could be separated into two, linked QTLs in repulsion phase with dominant gene action [39,40] conducted a QTL mapping study using 3 recombinant inbred populations using a North Carolina Design III approach. The results of this study were consistent with previous studies in maize.…”
Section: A Case For the Dominance Hypothesis: Early 1900s To Presentmentioning
confidence: 99%